A Review of Potential on Modified Binder with Glass Cullet as Fine Aggregate Replacement - ROSLI, AMY EMILYANA; SARIF, ABD SUKOR (Progress in Engineering Application and Technology, 2021)
In Malaysia, the amount of glass waste generated every year continuously increased has led to a major problem in landfill areas due to its classification as non-biodegradable waste which harms the environment. Besides, the usage of raw aggregates resulted in limited supply and getting more costly in the market. Glass cullet is also known as the recycled crushed glass can be substituted for fine aggregates to reduce the consumption of natural aggregates in road paving. Therefore, this study was conducted to examine the potential of glass cullet as a replacement of fine aggregate in road pavement. The laboratory testing that was performed is Marshall Stability-Flow Test where the asphalt mixture with optimum glass content varying from 5%, 8%, 10%, and 15% glass as a fine aggregate replacement has been observed to perform better than the conventional asphalt. From this study, the optimum glass percentage of 8% is acceptable with the Jabatan Kerja Raya (JKR) standard specifications and it is recommended to be applied in the road pavement. By using glass cullet, not only it could reduce the production cost of natural aggregates, but also minimize the disposal of glass waste at the landfills.